2020
DOI: 10.1002/ped4.12231
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS‐CoV‐2 infections among children visiting a hospital

Abstract: Importance In this study, we retrospectively investigated the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies within serum samples from children in Beijing, China. These findings provide preliminary guidance regarding population susceptibility to SARS‐CoV‐2, which will aid in establishing policy toward coronavirus disease 2019 (COVID‐19) prevention and control. Objective To understand the seropositivity of anti‐SARS‐CoV‐2 IgM/Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Our results revealed that the seropositivity rate in children is similar according to sex, with 61.8% seropositivity observed in males and 55.2% in females. This result is inconsistent with finding of previous study that reported higher seropositivity rate in boys than girls [ 23 ]. However, our previous study found a higher SARS-CoV-2 viral load (based on lower Ct values) among females compared with males [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results revealed that the seropositivity rate in children is similar according to sex, with 61.8% seropositivity observed in males and 55.2% in females. This result is inconsistent with finding of previous study that reported higher seropositivity rate in boys than girls [ 23 ]. However, our previous study found a higher SARS-CoV-2 viral load (based on lower Ct values) among females compared with males [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, no recent studies have evaluated anti-SARS-CoV-2 antibodies prevalence in Italy in the same period, so we lack data for a comparison. Of note, no significant differences in anti-SARS-CoV-2 IgG positivity were found in a large pediatric cohort evaluated in China over a 6-month period between March and August 2020 [ 19 ]. Data from sero-surveillance programmes implemented in England similarly showed a plateau in seropositivity in children between January and August 2021, followed by a large increase starting from September 2021, probably due to the deployment of the vaccination campaign [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is an increase in IgG specific B‐cell rates in children with SARS‐CoV‐2, indicating a rapid and effective humoral immune response. 65 , 66 In a seroprevalence pediatric study ( n = 208), children aged 10–16 years have 2–3 times higher positive antibody titers than children under 10 years old. 67 Possible etiologies that enhance the innate immune response and humoral activity constitute a) the decreased expression of the ACE2 receptor in the upper respiratory epithelium of younger children and b) the antibody cross‐reactivity with other common cold CoVs, in which older children are more frequently exposed to.…”
Section: Humoral Immunitymentioning
confidence: 99%
“…Children often experience robust antibody production within the first 3 weeks post infection and an estimated seroconversion time to IgG antibodies in the first week. Additionally, there is an increase in IgG specific B‐cell rates in children with SARS‐CoV‐2, indicating a rapid and effective humoral immune response 65,66 . In a seroprevalence pediatric study ( n = 208), children aged 10–16 years have 2–3 times higher positive antibody titers than children under 10 years old 67 .…”
Section: Humoral Immunitymentioning
confidence: 99%